2019
DOI: 10.5125/jkaoms.2019.45.5.267
|View full text |Cite
|
Sign up to set email alerts
|

Role of immunoreactive patterns of lymph nodes in neck dissection cases of oral squamous cell carcinoma: a clinical and histopathological study

Abstract: ObjectivesMetastasis in oral squamous cell carcinoma (OSCC) can occur in a variety of ways, and draining lymphatics and lymph nodes serve as a common route. Prior to metastasis, lymph nodes elicit an immune response to either wall off or create a favorable environment for homing of tumor cells. This immune response to tumor stimuli is visualized by recognizing various immunoreactive patterns exhibited by the lymph node. The present study aims to evaluate the role of immuno-morphologic patterns of the lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Bhatlande et al supposed that immunoreactive patterns including sinus histiocytosis of the LN was relative to favorable environment for homing tumor cells and emphasized some nodal histological patterns correlated with tumor grade in OSCC, and necessity of LN patterns for sentinel LN biopsies and neck dissections for OSCCs (Bhatlawande et al, 2019). We hypothesized that microenvironment as a pre-metastatic niche was required for lymphatic metastasis from primary OSCC and that ECM remodeling was needed to build the microenvironment.…”
Section: Ta B L E 4 Correlation Between Expressions Of Ecm-remodelingmentioning
confidence: 89%
“…Bhatlande et al supposed that immunoreactive patterns including sinus histiocytosis of the LN was relative to favorable environment for homing tumor cells and emphasized some nodal histological patterns correlated with tumor grade in OSCC, and necessity of LN patterns for sentinel LN biopsies and neck dissections for OSCCs (Bhatlawande et al, 2019). We hypothesized that microenvironment as a pre-metastatic niche was required for lymphatic metastasis from primary OSCC and that ECM remodeling was needed to build the microenvironment.…”
Section: Ta B L E 4 Correlation Between Expressions Of Ecm-remodelingmentioning
confidence: 89%
“…Hence our findings supports the fact that the presence of SH indicates more advanced stage of carcinoma (Ioachim and Medeiros, 2009). It is also being associated with the poorer patient prognosis and Tumour invasion ( Bhatlawande et al, 2019) Of the 255 nodes harvested from WDSCC cases in the present study (Table 2), 74.22% (p< 0.005) LNs showed GCP pattern, 69% lymphocyte predominance (p< 0.0003). Suchitra et al, 2015 in their study on OSCC correlated LP with survival rate and found to have a significant association with mortality and improved 5 year survival rate.…”
Section: Resultsmentioning
confidence: 63%
“…Previous studies have observed tumor progression may aid in release of antigens which can bring a typical immune response in the LN and LP and GCP are early immunological response to antigenic insult. With metastasis LP is replaced by SH and LD pattern and these changes may help to determine disease prognosis (Bhatlawande et al, 2019) There is insufficient literature on individual morphological pattern of lymph node associating with TNM staging, Grading and MVA. Assessment of these parameters can be utilized in classifying the OSCC as high-risk and low-risk cases and planning various therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%